2015
DOI: 10.1111/pbi.12487
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome‐wide sequencing provides insights into geocarpy in peanut (Arachis hypogaea L.)

Abstract: Summary A characteristic feature of peanut is the subterranean fructification, geocarpy, in which the gynophore (‘peg’), a specialized organ that transitions from upward growth habit to downward outgrowth upon fertilization, drives the developing pod into the soil for subsequent development underground. As a step towards understanding this phenomenon, we explore the developmental dynamics of the peanut pod transcriptome at 11 successive stages. We identified 110 217 transcripts across developmental stages and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 61 publications
(71 reference statements)
1
36
0
Order By: Relevance
“…Next generation sequencing (NGS) methods have enabled the rapid and cost-efficient sequencing of plant genomes. In past several years, several studies have reported the development of genetic resources for peanut, including SSRs 14 , 27 , transcript sequences 28 , 29 , and draft nuclear genome sequences 1 , 3 . However, the chloroplast genome is non-recombining and uniparentally inherited, making it a valuable source of information for improving the phylogenetics, species identification, and resolution 18 , 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Next generation sequencing (NGS) methods have enabled the rapid and cost-efficient sequencing of plant genomes. In past several years, several studies have reported the development of genetic resources for peanut, including SSRs 14 , 27 , transcript sequences 28 , 29 , and draft nuclear genome sequences 1 , 3 . However, the chloroplast genome is non-recombining and uniparentally inherited, making it a valuable source of information for improving the phylogenetics, species identification, and resolution 18 , 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Geocarpy is a fascinating aspect of Arachis reproductive development. There have been studies investigating the gene expression during geocarpic development in peanut (Xia et al, 2013 ; Zhu et al, 2014 ; Chen et al, 2016 ). Zhu et al ( 2014 ) and Xia et al ( 2013 ) identified an up-regulation of photosynthesis in aerial pegs.…”
Section: Discussionmentioning
confidence: 99%
“…The gravitropic growth of the peanut gynophore is one of the most critical characteristics for peanut fructification, in which the peg, a specialized organ that transitions from upward growth habit to downward outgrowth upon fertilization, drives the developing pod into the soil for subsequent development underground [37,61,62]. It is still unknown why the aerially developing pod cannot swell normally as compared to that penetrate into soil, although a series of studies attempt to reveal this phenomenon through transcriptomics and proteomics [37,61,63]. Our results found that there was no significant difference in the expression level of SUMO pathway genes between the aerial peg stage and the subterranean peg stage.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the pod develops and a mature peanut pod is produced [35,36]. The subterranean fructification is the most prominent characteristic of seed production in peanut and thus has the biologically important for studying organogenesis and evolution [37]. Additionally, peanut often cultivated in the semiarid tropical regions, are often exposed to water stress (mid-season and end-season) and high temperature (> 34°C) during the critical stages of flowering and pod development [38].…”
Section: Introductionmentioning
confidence: 99%